Duck Egg Hatching Incubator Technology Based On Internet of Things - Kurniawan, Medy Dwi; Styawati, Styawati; Hepri, Alfian (LPPM STIKI Malang, 2024)
The egg incubator was originally a simple tool using a lamp to produce heat without other supporting tools, So the incubation process has a big influence on traditional egg hatching through the mother duck incubating the eggs. However, temperature control at the time Incubation of eggs by the parent certainly has certain limitations due to the parent which is difficult to control in order to incubate it which ultimately causes the egg to suffer hatch failure. In the process of hatching duck eggs, you must pay attention to temperature and humidity and egg rotation which must be maintained regularly, is necessary continuous supervision and monitoring so that the eggs can hatch well. By utilizing applicable Internet of Things technology in the field of animal husbandry, it is a solution to monitor the condition of hatching duck eggs automatic and real-time, so it can help farmers in monitoring conditions such as temperature and humidity as well as the condition of the eggs in the hatching room. So A research was conducted entitled